1984
DOI: 10.1063/1.864699
|View full text |Cite
|
Sign up to set email alerts
|

Wave excitation and fast ion generation in a double plasma device

Abstract: Wave excitation and fast ion generation in a double plasma device are studied experimentally. Results show how a compressive density perturbation, propagating as a wave, is formed in the target plasma when a positive potential pulse is externally applied. Further, it is shown that fast ions are generated in a narrow plasma region close to the sheath near the grid because of reflection by the wave front during propagation of the wave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The ion temperature was not directly measured in the present experiment. Other experiments 34,35 had reported T i Ϸ 0.1 eV or T i Ϸ 0.2 eV under similar conditions. Deviations from room temperature were attributed to heating by gas friction in the presence of an electrostatic field.…”
Section: A Details Of Data Acquisitionmentioning
confidence: 54%
“…The ion temperature was not directly measured in the present experiment. Other experiments 34,35 had reported T i Ϸ 0.1 eV or T i Ϸ 0.2 eV under similar conditions. Deviations from room temperature were attributed to heating by gas friction in the presence of an electrostatic field.…”
Section: A Details Of Data Acquisitionmentioning
confidence: 54%
“…It should be noted here that a ''negative'' density pulse appears at such small distances in the case of the DP excitation. 2 The difference between the two cases may result from different ways of ion injection from the driver side to the target one, as will be described later. Furthermore, it is known from Fig.…”
Section: B Excitation Of Solitary Waves By Applying External Pulsesmentioning
confidence: 99%
“…3, which is almost equal to the ion-acoustic velocity as observed in a conventional DP device. 2,3 Other characteristics of excited waves will be described in the next section.…”
Section: B Excitation Of Solitary Waves By Applying External Pulsesmentioning
confidence: 99%
“…Since Ikezi et al 1 observed an ionacoustic solitary wave in a double plasma machine, several authors have studied ion-acoustic solitary waves in laboratory experiments 2-9 as well as in particle-in-cell (PIC) simulations. [10][11][12][13][14] For instance, Nagasawa and Nishida 6 carried out experimental observations on the nonlinear reflection and refraction of a planar ion-acoustic solitary wave in a double plasma device. Lee et al 7 found a chain of solitary waves in a double plasma device, the characteristics of which agree well with the solution of the KdV equation for ion-beam plasma systems.…”
Section: Introductionmentioning
confidence: 99%